2023
DOI: 10.1364/opticaopen.21967049.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated photoelasticity measurements of a three-dimensional laminar flow: second-order stress terms in the stress-optic law

Abstract: This study experimentally validates a stress-optic law for a three-dimensional flow using integrated photoelasticity. In this stress-optic law, the stress is related to the two photoelastic parameters — the phase retardation Δ and orientation 𝜙 — of elliptically-polarized light. Previous studies have examined the stress-optic law of three-dimensional flows, but the importance of the second-order stress terms in the three-dimensional stress-optic law, i.e., those relating to the stress component along the came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…These experimental findings have also been verified by numerical calculations, which established that the regions in which the impact of 3D effects are found to be dominant are close to the plane of symmetry 16 . This phenomenon has been reported in circular and rectangular channels with aspect ratios close to 1 [17][18][19] . It has been concluded that this is due to shear on the upper and lower surfaces of the channel, although quantitative insights were limited.…”
Section: Introductionsupporting
confidence: 69%
“…These experimental findings have also been verified by numerical calculations, which established that the regions in which the impact of 3D effects are found to be dominant are close to the plane of symmetry 16 . This phenomenon has been reported in circular and rectangular channels with aspect ratios close to 1 [17][18][19] . It has been concluded that this is due to shear on the upper and lower surfaces of the channel, although quantitative insights were limited.…”
Section: Introductionsupporting
confidence: 69%
“…Fitting was also conducted in different cases, and it was verified that the magnitude of C 2 was O(10 −7 -10 −6 ). Note that C 1 values for fluids have been reported to be O(10 −7 -10 −5 ) in previous studies (Ito et al 2016;Nakamine et al 2023). Although their units are different and therefore need to be discussed, C 1 and C 2 were found to be of similar magnitudes.…”
Section: Resultsmentioning
confidence: 67%
“…This can be explained as being due to the shear caused by the upper and lower surfaces of the channel wall. This discrepancy between theory and experiment is more significant in the case of three-dimensional flows, where the contribution of the shear components along the optical axis is larger (Kim et al 2017;Nakamine et al 2023).…”
mentioning
confidence: 90%